Respuesta :

Answer:

y + 6 = (-8/5)(x - 1) in point-slope form

Step-by-step explanation:

Moving from the 1st point to the first, we see that x (the 'run') increases by 5 from -4 to 1, and y (the 'rise') decreases by 8.  Thus, the slope of the line through these two points is m = rise / run = -8/5

Now we have two points on the line, plus the slope.  Let's write out the point-slope formula for the equation of a straight line:

y - k = m(x - h), where (h, k) is a point on the line and m is the slope of the line.

Here, using the point (1, -6), we obtain:

y + 6 = (-8/5)(x - 1) in point-slope form

ACCESS MORE